On the Vocabulary in the Unpublished Second Volume of the Bulgarian Explanatory Dictionary by Stefan Mladenov - Благоева, Диана (Języki słowiańskie dziś: w kręgu kategorii, struktur i procesów, 2021)
This article is devoted to the unpublished second volume of the Bulgarian Explanatory Dictionary by Stefan Mladenov and the key principles guiding the creation of its headword list. Following the Dictionary of the Bulgarian Language by Naĭden Gerov and the Dictionary of the Bulgarian Language Based on Folk Literary Heritage and Publications of Today’s Press by Aleksandr Duvernois, Mladenov’s dictionary marks the next stage in the development of Bulgarian lexicography. It presents a full picture of both literary and dialectal vocabulary and provides rich material for the study of Bulgarian lexis from the first decades of the last century. The lexical material included in the unpublished second volume of the Bulgarian Explanatory Dictionary indicates that in the early twentieth century Bulgarian dialects continued to be the main source which contributed to the enrichment of the Bulgarian literary language. The vocabulary included in the Bulgarian Explanatory Dictionary also sufficiently documents the role of lexical borrowing from Western European and (to a lesser extent) Slavic languages in expanding Bulgarian lexis in the period. The stylistic aspect of the lexis is also reflected in the volume, though not quite consistently and systematically.